2016
DOI: 10.1097/cej.0000000000000195
|View full text |Cite
|
Sign up to set email alerts
|

Role of high-fat diet on the effect of pioglitazone and melatonin in a rat model of breast cancer

Abstract: The risk of cancer may be modulated by drugs with pleiotropic effects and diet has been implicated in the efficacy of treatment. The oncopreventive effects of the antidiabetic drug pioglitazone (PIO) and the anti-insomnia drug melatonin (MT), in vivo, have been proven before, but using a standard-type diet. This study evaluated the impact of a high-fat diet on their efficacy in chemically induced mammary carcinogenesis in Sprague-Dawley rats. Mammary tumours were induced by N-methyl-N-nitrosourea (50 mg/kg, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…In an animal study, rosiglitazone suppresses mammary tumor growth in rats treated with the carcinogen 7,12-dimethylbenz(a)anthracene [ 20 ]. On the other hand, although pioglitazone inhibits aromatase expression by inhibiting proinflammatory prostaglandin E2 signaling and upregulating tumor-suppressor gene BRCA1 [ 21 ], it does not inhibit mammary tumor growth induced by N-methyl-N-nitrosourea in Sprague-Dawley rats fed a high-fat diet [ 22 ]. Studies also suggested that metformin and pioglitazone might have different effects on breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal study, rosiglitazone suppresses mammary tumor growth in rats treated with the carcinogen 7,12-dimethylbenz(a)anthracene [ 20 ]. On the other hand, although pioglitazone inhibits aromatase expression by inhibiting proinflammatory prostaglandin E2 signaling and upregulating tumor-suppressor gene BRCA1 [ 21 ], it does not inhibit mammary tumor growth induced by N-methyl-N-nitrosourea in Sprague-Dawley rats fed a high-fat diet [ 22 ]. Studies also suggested that metformin and pioglitazone might have different effects on breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pharmacological intervention is initiated at different time points relative to cancer initiation and study durations are mixed. Positive impacts provide support for the principle of PPARG agonist chemoprevention (Kocdor et al 2009, Li & Brown 2009, McCormick et al 2015, Ory et al 2018 but when significant effects are limited to hyperplasia and/or preneoplasia, alterations in cancer histology and/or mean tumor volume, there is less enthusiasm (Borbath et al 2007, Wu et al 2008, Skelhorne-Gross et al 2012, Nakles et al 2013, Bojková et al 2016, Alothman et al 2018. Occasional published studies report no effect at all (Yee et al 2005).…”
Section: Interactions Between Pparg and Brca1mentioning
confidence: 99%
“…Although parameters of tumor growth were not significantly changed, pioglitazone alone decreased proportion of HG tumors and increased apoptosis in mammary cancer cells. MEL potentiated the effect of pioglitazone as evidenced by decrease in tumor frequency and further reduction in HG/LG ratio (Table S1, [325]).…”
Section: Pleiotropic Drugs and Mel In Cancer Prevention/treatmentmentioning
confidence: 99%